The plasma microRNA levels and their relationship with the general health and functional status in female patients with fibromyalgia syndrome - Erbil Akaslan; Orhan Güvener; Ayşegül Görür; Didem Havva Çelikcan; Lülüfer Tamer; Ali Biçer (Archives of Rheumatology, 2021)
Objectives: The aim of this study was to identify the plasma level of micro-ribonucleic acid (microRNA) expressions and the relationship between plasma microRNA levels with the general health and functional status in female patients with fibromyalgia syndrome (FMS). Patients and methods: Thirty-five female patients (mean age: 42.0±11.8 years; range, 21 to 62 years) diagnosed as FMS and 35 sex-and age-matched healthy controls (mean age: 43.7±8.8 years; range, 21 to 56 years) were enrolled in the study. MicroRNA measurements of the participants in plasma were carried out by using the quantitative polymerase chain reaction (qPCR). A total of 11 plasma levels of microRNA expressions were examined in both groups. The general health and functional status of the patients and controls were assessed by the Fibromyalgia Impact Questionnaire (FIQ) and the Short Form-36 (SF-36) scale. Results: No significant difference was observed between the plasma levels of microRNA expressions in patients with FMS and healthy controls. The plasma level of miR-320a expression was found to be negatively correlated with the total FIQ score in female patients with FMS (p=0.05, r=-0.34). Negative correlations were also detected between the plasma level of miR-320a and miR-320b expressions and the subscale score of SF-36 physical function in female patients with FMS (p=0.01, r=-0.43 and p=0.01, r=-0.43, respectively). A strong positive correlation was found between miR-142-3p and the subscale score of SF-36 mental symptom score in female patients with FMS (p<0.001, r=1.00). Conclusion: The expression levels of microRNAs in plasma between female patients with FMS and controls were not significantly different. Only plasma levels of miR-320a, miR-320b, and miR-142-3p expressions were associated with the general health, functional status, and mental symptom score in female patients with FMS.